Environmental implications of metal mobility in marine sediments receiving input from a torrent affected by mine discharge. (February 2019) - Consani, Sirio; Ianni, Maria Carmela; Cutroneo, Laura; Dinelli, Enrico; Carbone, Cristina; Capello, Marco
Abstract: Acid Mine Drainage (AMD) is one of the most important sources of pollution in fluvial systems and can enrich rivers in dissolved and suspended metals of environmental concern. Colloidal particles may favour the transport of metals to the sea, where metals can be accumulated in bottom sediments. The aim of this paper was to evaluate the mobility of metals in the "Baia delle Favole" bottom sediments (Sestri Levante, Italy), which receive the input of the AMD impacted Gromolo Torrent, using chemical speciation (BCR sequential extraction). Basing on the Risk Assessment Code (RAC), our results showed a systematic and widespread high risk classification for Mn, whereas a medium risk is associated to Co, Cu, and Zn in the sediments collected near the mouth of the Gromolo Torrent. Moreover, in these sediments the occurrence of Fe oxyhydroxides has been observed, reflecting an increase of metals in the reducible fraction obtained with BCR. Highlights: The mobility of metals in marine sediments has been tested. Mn is bound to carbonates and showed widespread high risk classification with RAC. Pb was readily extracted in bay sediments and is bound to Fe oxyhydroxides. Co, Cu, and Zn showed a medium risk in sediments near the torrent mouth.